The effect of Grammarly-assisted repetition method on students’ learning motivation and English writing ability - Al Hadid Nur Rahim; Fetri Yeni; Rayendra Rayendra; Darmansyah Darmansyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study aimed to examine the effectiveness of integrating Grammarly with the assignment reiteration method in improving students’ learning motivation and English writing skills at SMA Negeri 14 Batam. This research employed a quantitative quasi-experimental design involving an experimental and a control group. The participants were selected through purposive sampling from 11th-grade students with low English writing proficiency. Data were collected using a writing test and a learning motivation questionnaire and analyzed through paired-sample and independent-sample t-tests. The findings revealed that students in the experimental group showed higher improvement in learning motivation, with mean scores increasing from 33.44 to 38.22, compared to the control group (33.51 to 35.63). Writing skills also improved significantly in the experimental group, with mean scores rising from 16.78 to 19.31, while the control group increased from 16.61 to 17.68. The posttest analysis showed significant differences between groups (p < 0.05). The study concludes that Grammarly integrated with assignment reiteration effectively enhances students’ motivation and English writing performance through continuous feedback and iterative revision.